المعوقات الذاتية التي تواجه مجلس الامن في تدويل النزاعات الداخلية - محمد خالد برع (PROSPECTIVE RESEARCHES, 2023)
Internal conflicts are one of the most serious problems facing the UN Security Council due to the legal nature of these conflicts and the role of states in orienting them in a way that serves their own interests. This leads to a clash in view points and then twisting legal texts in a way that serves them. From these points of departure, light is shed in this paper on the main obstacts facing the Security Council represented by obstacles pertaining to Security – Council membership and its mechanisms and the extent of its modification. In addition, the obstacles related to the mechanisms of voting in the council are considered, which are often governed by the interests by states which enjoy the right to vote irrespective of the prevailing interntional laws and orders. The paper will also focus on the right to veto whish is a double – edged weapon which permanent members enjoy. Through which those states can have the right of intervention or non-intervotionin any internal conflict, and then find approperate solutions to avoid any threat to international peace and secuiry.